Hyaluronic Acid-Binding, Anionic, Nanoparticles Inhibit ECM Degradation and Restore Compressive Stiffness in Aggrecan-Depleted Articular Cartilage Explants - Marcus Deloney; Parssa Garoosi; Vanessa F. C. Dartora; Blaine A. Christiansen; Alyssa Panitch (MDPI AG, 2021)
Joint trauma results in the production of inflammatory cytokines that stimulate the secretion of catabolic enzymes, which degrade articular cartilage. Molecular fragments of the degraded articular cartilage further stimulate inflammatory cytokine production, with this process eventually resulting in post-traumatic osteoarthritis (PTOA). The loss of matrix component aggrecan occurs early in the progression of PTOA and results in the loss of compressive stiffness in articular cartilage. Aggrecan is highly sulfated, associates with hyaluronic acid (HA), and supports the compressive stiffness in cartilage. Presented here, we conjugated the HA-binding peptide GAHWQFNALTVRGSG (GAH) to anionic nanoparticles (hNPs). Nanoparticles conjugated with roughly 19 GAH peptides, termed 19 GAH-hNP, bound to HA in solution and increased the dynamic viscosity by 94.1% compared to an HA solution treated with unconjugated hNPs. Moreover, treating aggrecan-depleted (AD) cartilage explants with 0.10 mg of 19 GAH-hNP restored the cartilage compressive stiffness to healthy levels six days after a single nanoparticle treatment. Treatment of AD cartilage with 0.10 mg of 19 GAH-hNP inhibited the degradation of articular cartilage. Treated AD cartilage had 409% more collagen type II and 598% more GAG content than untreated-AD explants. The 19 GAH-hNP therapeutic slowed ECM degradation in AD cartilage explants, restored the compressive stiffness of damaged cartilage, and showed promise as a localized treatment for PTOA.